Mapping the colorectal tumor microbiota. (1st January 2021) - Murphy, CL; Barrett, M; Pellanda, P; Killeen, S; McCourt, M; Andrews, E; O' Riordain, M; Shanahan, F; O'Toole, Pw
ABSTRACT: The gut microbiome in patients with colorectal cancer (CRC) is different than that of healthy controls. Previous studies have profiled the CRC tumor microbiome using a single biopsy. However, since the morphology and cellular subtype vary significantly within an individual tumor, the possibility of sampling error arises for the microbiome within an individual tumor. To test this hypothesis, seven biopsies were taken from representative areas on and off the tumor in five patients with CRC. The microbiome composition was strikingly similar across all samples from an individual. The variation in microbiome alpha-diversity was significantly greater between individuals' samples then within individuals. This is the first study, to our knowledge, that shows that the microbiome of an individual tumor is spatially homogeneous. Our finding strengthens the assumption that a single biopsy is representative of the entire tumor, and that microbiota changes are not limited to a specific area of the neoplasm.